The ADDIE Method in Digital Atlas-Based Learning Media on Practicum Learning Outcomes in Histology of Medical Students - Paramata, Nanang Roswita; Nisa, Hasna Qurrotun; Hasanuddin, Abdi Dzul Ikram; Isa, Abdul Hamid (PPSDP International Journal of Education, 2024)
Histology is one of the basic sciences that is difficult to learn, as evidenced by low practicum scores. The purpose of this research is to develop histology digital atlas-based learning media for medical students at Universitas Negeri Gorontalo. This digital atlas-based media aims to enhance student learning outcomes. The ADDIE method was used to develop the learning media. The results show an improvement in the learning outcomes of medical students in the histology practicum. It implies to use ADDIE for everyone who wants to develop learning media. It contributes to all teachers to use ADDIE method in Digital Atlas based learning media on practicum learning outcome.